Feasibility of free space quantum key distribution with coherent polarization states - Elser, D; Bartley, T; Heim, B; Wittmann, C; Sych, D; Leuchs, G (2009)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.